Fifth International Bridge Engineering Conference. - National Research Council (U.S.). Transportation Research Board; International Bridge Engineering Conference 2000 Tampa, Florida). (Washington, D.C. National Academy Press, 2000)
"Papers presented at the Fifth International Bridge Engineering Conference, April 3-5, 2000, Tampa, Florida."
"A peer-reviewed publication of the Transportation Research Board."
"Transportation Research Board, National Research Council."
"January 2000"--P. [2] of cover.
Includes bibliographical references.
Keywords: Bridges -- Design and construction -- Congresses